Effect of Wearing Surgical Face Masks During Exercise: Does Intensity Matter? - Poon, Eric Tsz-Chun; Zheng, Chen; Wong, Stephen Heung-Sang (Frontiers in Physiology, 2021)
Face masks are widely recommended as means of controlling the coronavirus disease outbreak. This study aimed to examine the physiological and perceptual responses of wearing surgical face masks while exercising at different intensities. Thirteen healthy young adults (mean age, 21.9 ± 1.4 years) conducted randomized crossover trials with or without a surgical face mask. In each trial, participants completed an incremental treadmill protocol, with three 6-min stages (light, moderate, and vigorous at 25, 50, and 75% maximal oxygen uptake, respectively). Physiological outcomes (heart rate, blood lactate, and oxygen saturation level), perceived exertion and discomfort feeling were assessed. No significant differences were observed in physiological outcomes with or without masks at different exercise intensities (p>0.05). However, the rating of perceived exertion was significantly higher when exercising vigorously (mask: 15.5 ± 1.5 vs. no-mask: 14.2 ± 2.1, p<0.05). Participants wearing masks reported marked discomfort, such as feeling hot, humid, and breathing resistance. Although face mask-wearing during exercise may not have detrimental effects on major physiological parameters, it can increase perceived exertion level and discomfort when the exercise intensity exceeds a certain threshold. Therefore, healthcare professionals should cautiously evaluate each person’s ability to exercise while wearing a mask and tailor their prescription accordingly.